A systematic review of the role of integrated farming and the participation of universities in ensuring food security: Malaysia’s effort - Mohamed Thariq Hameed Sultan; Farah Syazwani Shahar; Mohd Izani Mohd Zain; Ibrahim Komoo (Italian Journal of Food Safety, 2024)
Food security is critical for promoting health and well-being and achieving sustainable development, especially in developing countries. Despite the recent efforts to improve it, food security is still a concern due to the rapid increase in populations, conflicts, and natural disasters worldwide. Universities, particularly agricultural universities, play an essential role in addressing food security issues by researching, developing new technologies, and providing education and training to farmers and other stakeholders. The main objective of this review is to discuss the role of universities and integrated farming in ensuring food security. Specifically, this paper reviews the importance of universities and focuses on their role in ensuring and promoting food security in Malaysia. It includes a brief overview of the different types of integrated farming methods that can be used to improve food security and finally discusses the Student Farmer Entrepreneur program, which can be crucial in promoting food security by increasing agricultural productivity, promoting local food production, encouraging sustainable agriculture practices, and supporting rural development. This review also considers the significant impact of the Malaysian government and universities on food security. With integrated farming and the Student Farmer Entrepreneur program, food security can be further improved.